Devlopment of DC-DC converter for car adapter - Mohamad Nazrin bin Amin Salleh (Department of Electronic Engineering Technology, Faculty of Engineering Technology, University Malaysia Perlis, 2015)
This project focuses on the designing and developing a switched-mode power supply (SMPS) DC-DC buck converter for car charger adapter to charge up electronic devices. In order for the devices to be charged, the charger output must be above 3.7V. By using buck converter, the input voltage of 12 V from car battery can be reduced to 5V that is needed to charge the phone. The purpose of the project is to design a simple and efficient car charger for portable gadgets by using the SMPS DC-DC buck converter. Proteus software is used to simulate the circuit and to design the layout on the PCB for hardware implementation. The hardware was consist of three main components which are Pulse Width Modulator controller, buck converter and driver circuit.The output from the built dc-dc converter work with high efficiency above 90% and the output voltage was below 5V as expected due to the existence of switching and conduction voltage drop. Detailed analysis of the results is also presented in this report.